Viability of tallow inclusion in Atlantic salmon diet, as assessed by an on-farm grow out trial - JA Emery; R Smullen; Russell Keast; GM Turchini (2016)
The results of a recent increase in research interest directed at the inclusion of tallow in fish feed formulations are suggesting tallow is viable as a potential substitute for other alternative lipid sources such as poultry by-product oil. Although strong growth performance data has been shown, reservations still exist regarding reduced digestibility and the potential impacts this could have on performance over the duration of a grow-out period in low temperature conditions. Also little information is yet available on the potential effect of dietary tallow inclusion on final product quality. A large scale farm based study testing the inclusion of tallow at 40% inclusion, partially replacing poultry by-product oil, in commercial diets of Atlantic salmon over a winter grow-out period in southern Tasmania, Australia was conducted. Tallow inclusion had no impact on growth performance or nutrient digestibility. Tallow resulted in a slight improvement in fillet quality exhibiting a significant reduction in n - 6 PUFA and the n6:n3 ratio, and an increased n - 3LC-PUFA tissue deposition. Consumers were unable to display any preference in liking between 3 salmon products (cold smoked, hot smoked, and cooked) as a result of tallow inclusion. This study demonstrates the viability of partial inclusion of tallow in Atlantic salmon diets over a winter grow-out period. Statement of relevance: Improved knowledge of alternative dietary energy sources (oils and fats) to be used in aquafeed, (replacing the increasingly expensive, and diminishingly available, fish oil) is a key area of research towards improved environmental sustainability and economic viability of the aquaculture sector. Following a promising laboratory based, research scale, in vivo trial aimed at assessing the viability of tallow in salmon feed, a larger and longer duration farm-based trial was implemented to validate initial findings. Consumer test of final products (fresh-cooked, hot smoked and cold smoked fillets) showed no modification of sensorial ...